Immediate Debridement and Reconstruction with a Pectoralis Major Muscle Flap for Poststernotomy Mediastinitis - Yu Jin Jang (Archives of Plastic Surgery, 2012)
Background Poststernotomy mediastinitis is a rare, but life-threatening complication, thus early diagnosis and proper management is essential for poststernotomy mediastinitis. The main treatment for mediastinitis is aggressive debridement. Several options exist for reconstruction of defects after debridement. The efficacy of immediate debridement and reconstruction with a pectoralis major muscle flap designed for the defect immediately after the diagnosis of poststernotomy mediastinitis is demonstrated. Methods Between September 2009 and June 2011, 6 patients were referred to the Department of Plastic and Reconstructive Surgery and the Department of Thoracic and Cardiovascular Surgery of Ajou University Hospital for poststernotomy mediastinitis. All of the patients underwent extensive debridement and reconstruction with pectoralis major muscle flaps, advanced based on the pedicle of the thoracoacromial artery as soon as possible following diagnosis. A retrospective review of the 6 cases was performed to evaluate infection control, postoperative morbidity, and mortality. Results All patients had complete wound closures and reduced severity of infections based on the erythrocyte sedimentation rate and C-reactive protein levels and a reduction in poststernal fluid collection on computed tomography an average of 6 days postoperatively. A lack of growth of organisms in the wound culture was demonstrated after 3 weeks. There were no major wound morbidities, such as hematomas, but one minor complication required a skin graft caused by skin flap necrosis. No patient expired after definitive surgery. Conclusions Immediate debridement and reconstruction using a pectoralis major muscle flap is a safe technique for managing infections associated with poststernotomy mediastinitis, and is associated with minimal morbidity and mortality.